Does the presence of independent directors reduce the practices of earnings management? : the moderating role of family ownership concentration - Al-Deen Al-Sraheen, Deaa (Array, 2019)
While often criticized, the independence of directors remains a crucial criterion for evaluating the effectiveness of the monitoring role of boards. This study examines the relationship between board independence and earnings management, paying attention to moderation role of family ownership concentration on this relationship using a sample of services companies listed on Amman Stock Exchange ASE. This study documented a significant and negative association between board independence and earnings management. In addition, the moderating role of family ownership concentration on this relationship was also negative. Thus, the board’s monitoring function was inefficient due to the concentration of ownership. These results were obtained through using multiple and sequential regression analysis for the research data from 2013 to 2016. This study provides new ideas for future research such as examining the impacts of the migration of capitals and investors from neighbouring countries such as Syria and Iraq.